Forensic Pathology in Crime Scene Investigation: Recent Advances, Challenges, and Criminal Psychological Perspective - Dr. Ahilan Devarajan,; Dr Ruchi Sharma,; A. LATHA,; Gowri Manogari, (The Bioscan, 2025)
Forensic pathology serves as a cornerstone in modern criminal investigations, bridging medical science and legal inquiry to determine the cause, manner, and mechanism of death. Over the past two decades, advancements such as postmortem imaging (computed tomography and magnetic resonance), molecular autopsies employing next-generation sequencing, and digital autopsy techniques have revolutionized the practice, offering non-invasive, rapid, and highly detailed analyses. Concurrently, the integration of criminal psychological insights—through behavioral profiling, psychological autopsies, and neuroimaging—has enriched the interpretive framework, enabling investigators to contextualize physical findings within offender motivations and cognitive patterns. However, these innovations pose multifaceted challenges: ethical considerations regarding consent and privacy, legal hurdles to admissibility under standards like Daubert, and disparities in resource availability across jurisdictions. This review synthesizes recent technological and psychological advances in forensic pathology, examines pivotal ethical and legal dilemmas, and highlights the imperative of interdisciplinary collaboration. A dedicated case studies section illustrates practical applications and limitations in real-world investigations. Finally, we propose future directions emphasizing standardized protocols, robust validation studies, and integrated training programs to ensure that forensic pathology continues to evolve as a rigorous, ethically sound, and psychologically informed discipline.